PVT1 affects growth of glioma microvascular endothelial cells by negatively regulating miR-186. Issue 3 (March 2017) - Ma, Yawen; Wang, Ping; Xue, Yixue; Qu, Chengbin; Zheng, Jian; Liu, Xiaobai; Ma, Jun; Liu, Yunhui
Vigorous angiogenesis is one of the reasons for the poor prognosis of glioma. A number of studies have shown that long non-coding RNA can affect a variety of biological behaviors of tumors. However, the influence of long non-coding RNAs on glioma vascular endothelial cells remains unclear. To simulate the glioma microenvironment, we applied glioma-conditioned medium to human cerebral microvascular endothelial cells. The long non-coding RNA PVT1 was found to be highly expressed in glioma vascular endothelial cells. Cell Counting Kit-8, migration, and tube formation assays showed that PVT1 overexpression promoted glioma vascular endothelial cells proliferation, migration, and angiogenesis. We also found that PVT1 overexpression upregulated the expression of the autophagy-related proteins Atg7 and Beclin1, which induced protective autophagy. Bioinformatics software and dual-luciferase system analysis confirmed that PVT1 acts by targeting miR-186. In addition, our study showed that miR-186 could target the 3′ untranslated region of Atg7 and Beclin1 to decrease their expression levels, thereby inhibiting glioma-conditioned human cerebral microvascular endothelial cell autophagy. In conclusion, PVT1 overexpression increased the expression of Atg7 and Beclin1 by targeting miR-186, which induced protective autophagy, thus promoting glioma vascular endothelial cell proliferation, migration, and angiogenesis. Therefore, PVT1 and miR-186 can provide new therapeutic targets for future anti-angiogenic treatment of glioma.